Thematic analysis of narrated reasons for suicidal ideation among Chinese adolescents in psychological counseling - Guo, Li; Zhang, Nan; Chen, Shuzhen (Frontiers in Psychiatry, 2025)
BackgroundAdolescent suicidal ideation is a critical public health concern in China, yet the subjective drivers of these thoughts remain insufficiently understood.ObjectiveThis study sought to elucidate the reasons Chinese adolescents articulate for suicidal ideation in real‐world counseling contexts.MethodsWe performed a reflexive thematic analysis of therapy transcripts from 51 adolescents (aged 10–19 years; 38 females and 13 males) seeking counseling for depressive symptoms, recruited from the psychiatric outpatient departments of Grade A tertiary hospitals in China.ResultsThe analysis identified five interconnected themes: (1) self-cognitive dissonance, (2) academic pressure, (3) family factors, (4) mental health issues (referring to the direct impact of their mental health symptoms), and (5) weak social ability. The findings reveal that these themes operate as a synergistic system, creating a reinforcing cycle where external pressures exacerbate internal vulnerabilities. For these adolescents, suicidal ideation appears to emerge from the complex interplay of academic, familial, social, and intrapsychic distress.ConclusionsThe results provide a nuanced understanding of how multiple risk factors synergize in this population and underscore the necessity of adopting integrated, multi-systemic interventions that concurrently target the adolescent’s cognitions, their family dynamics, and the school environment to effectively address this multifaceted crisis.